A SURVEY ON THE APPROPRIATE USE OF NON INVASIVE LIVER SCREEN BY GASTROENTEROLOGY TRAINEES IN WEST AND SOUTH YORKSHIRE, UK. (8th June 2013) - Lau, S Y M; Riyaz, S; Harrison, L
Abstract : Introduction: Non invasive liver screen (NILS) is an important commonly performed investigation by gastroenterologistsTable 1 . Aims/Background: We aimed to evaluate the appropriate use of NILS by gastroenterology trainees in South and West Yorkshire, UK, to assess whether training in this topic was adequate. Method: We devised a survey containing 2 scenarios regarding liver function derrangement and sent it to all 48 gastroenterology trainees in South and West Yorkshire. Trainees were asked to provide their year of training, experiences in liver units, if they had received teaching on NILS, and the investigations they would perform for each scenario. The answers from all 12 respondents were collected and compared against the investigations that we believe were appropriate for each scenario. Results: Most trainees selected the majority of appropriate tests for incidental abnormal liver biochemistry, but proportionately less so for acute hepatitis. 42% (5) trainees inappropriately tested for alpha-fetoprotein (AFP) in isolated abnormal liver function, and 8% (1) tested for AFP in acute hepatitis. 33% (4) inappropriately selected A-1 antitrypsin to investigate acute hepatitis. Interestingly, no significant difference in the number of correct answers was seen in trainees who had liver unit experience (mean 13, range 9–15) compared to those who did not (mean 12, range 6–14). Similarly, teaching on NILS (mean 12, range 9–15), or the lack of (mean 11, range 6–14), did not demonstrate a significant difference in the number of correct responses. Conclusion: NILS is essential to hepatology and thus sound knowledge is necessary. Improving teaching quality and mandatory training may support achievement of this target.